COVID-19 and necessity-based online entrepreneurship education at US community colleges. Issue 6 (15th June 2021) - Liguori, Eric W.; Winkler, Christoph; Zane, Lee J.; Muldoon, Jeff; Winkel, Doan
Abstract : Purpose: This paper explores community college entrepreneurship education's near-instantaneous transition to online course delivery following the 2020 COVID-19 pandemic. Design/methodology/approach: Primary data were obtained from 92 community college entrepreneurship faculty via online survey in late March of 2020, right at the time faculty were required to transition their courses to an online mode of delivery due to the COVID-19 pandemic. Data were collected in partnership with the National Association for Community College Entrepreneurship and the Entrepreneurship Education Project. Findings: While the majority of community college entrepreneurship educators have taught online previously, many were not familiar with exemplar education technology tools and applications, demonstrating an opportunity for continued professional development. To deliver courses online, educators primarily relied on pre-recorded lectures and using Zoom as the technology platform of choice. Last, there were significant faculty concerns about their ability to effectively create an "experiential" classroom virtually for students to learn and practice entrepreneurship. Originality/value: This is the first paper investigating how community college entrepreneurship educators responded to one of the most disruptive events to ever impact entrepreneurship education (viz. the COVID-19 pandemic). More broadly, this is also one of very few studies exploring both (1) community college entrepreneurship education and (2) how unexpected crises (e.g. natural disasters, pandemics) impact educational environments.